2022
DOI: 10.3390/ijms231911167
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Fingers and Homeobox Family in Cancer: A Double-Edged Sword

Abstract: The zinc fingers and homeobox (ZHX) family includes ZHX1, ZHX2, and ZHX3, and their proteins have similar unique structures, containing two C2H2-type zinc finger motifs and four or five HOX-like homeodomains. The members of the ZHX family can form homodimers or heterodimers with each other or with a subunit of nuclear factor Y. Previous studies have suggested that ZHXs can function as positive or negative transcriptional regulators. Recent studies have further revealed their biological functions and underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…We next focused on ZHX2, a protein of the zinc-fingers and homeoboxes (ZHX) family known to act as an oncogene in RCC in favor of proliferation and migration ( Figure 3 ) [ 12 , 13 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next focused on ZHX2, a protein of the zinc-fingers and homeoboxes (ZHX) family known to act as an oncogene in RCC in favor of proliferation and migration ( Figure 3 ) [ 12 , 13 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have indicated that ZHX2, a member of the ZHX (Zinc fingers and homeoboxes) family, has been involved in many types of cancer [ 12 ]. It has been reported that this transcription factor interferes with VHL regulation and evidence has been provided that shows it is associated with ccRCC initiation [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more evidence shows that ZHX2 is an important regulator of various biological processes, including regulating the development of various cancers such as liver cancer, gastric cancer, and thyroid cancer, and participating in lipid metabolism, cell differentiation, and development, NK cell maturation, and macrophage cell polarization, etc (33). Many literatures have reported that ZHX2 has an inhibitory effect on the proliferation and migration of different types of cells (17,21,(34)(35)(36)(37)(38)(39). Some literature reported that ZHX2 may be related to apoptosis (35,37).…”
Section: Discussionmentioning
confidence: 99%
“…The zinc fingers and homeobox (ZHX) family includes ZHX1, ZHX2, and ZHX3, and these proteins have similar unique structures, containing two C2H2-type zinc finger motifs and four or five HOX-like homeodomains (17). Previous studies have suggested that ZHXs can function as positive (18) or negative transcriptional regulators (19).…”
Section: Introductionmentioning
confidence: 99%